Enhancement of chemokine expression by interferon beta therapy in patients with multiple sclerosis - Cepok, Sabine; Schreiber, Herbert; Hoffmann, Steve; Zhou, Dun; Neuhaus, Oliver; Von Geldern, Gloria; Hochgesand, Sonja; Nessler, Stefan; Rothhammer, Veit; Lang, Michael; Hartung, Hans-Peter; Hemmer, Bernhard (Archives of Neurology, 2009)
Background: Interferon beta has been approved for the treatment of multiple sclerosis (MS). It is believed that immunomodulatory rather than antiviral activity of interferon beta is responsible for disease amelioration. The impact of interferon beta on the chemoattraction of immune cells has not been fully addressed. Objective: To address the influence of interferon beta on the expression of chemokines and their receptors in a standardized setting. Design: The expression of 14 chemokines and 14 chemokine receptor genes was determined by quantitative realtime polymerase chain reaction from fresh blood samples. Setting: Outpatient units in Germany. Patients: Untreated and interferon beta-treated patients with MS who tested positive and negative for neutralizing antibodies (NABs) were recruited from August 24, 2006, through December 15, 2006, for the initial study and from March 12, 2007, through April 2, 2007, for the validation study. Main Outcome Measures: Gene expression and serum chemokine protein levels. Results: CCL1, CCL2, CCL7, CXCL10, CXCL11, and CCR1 gene expression was strongly upregulated in interferon beta-treated, NAB-negative MS patients. In contrast, gene expression in interferon beta-treated, NAB-positive MS patients did not differ from untreated control donor individuals. Antibody titers inversely correlated with chemokine and chemokine receptor gene expression. Accordingly, serum chemokine protein levels of interferon beta-treated, NAB-negative MS patients were significantly higher than in untreated or interferon beta-treated, NAB-positive MS patients. Conclusions: We demonstrate that interferon beta strongly upregulates a set of chemokines and CCR1 in peripheral immune cells. The peripheral upregulation of these chemokines may reduce the chemoattraction of immune cells to the central nervous system and thus add to the therapeutic effects of interferon beta. ©2009 American Medical Association. All rights reserved.
CRIS-Team Scopus Importer:2020-09-22